Cryptocurrencies: the communication inside blockchain technology and the cross-border tax law. (20th August 2019) - Garcia, Andrea Romaoli; Garcia, Pedro Henrique Romaoli
This research aims to analyse the social event that is modifying the traditional financial system since the blockchain technology and cryptocurrencies came up. Taxation in international scenario were examined by the ideal from governments in a democratic system as an instrument that materialises human rights. The social observation approaches the legacy of Emile Durkheim philosophy who established a power relationship between social fact and coercion. Taxation has been the focal point in smart economy to juridical scientists and everyone involved in the digital economy. This research conducted tests and researches from historical and social method, seeking for laws, doctrine, jurisprudence and concrete case analysis in front of the philosophical school of logical-semantic constructivism as a suitable means to verify the possibility of constructing a matrix rule of tax incidence. This research was enough to show that the blockchain technology and cryptocurrencies fulfils its humanitarian role in the smart economy.